2016
DOI: 10.1016/j.jjcc.2015.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Modified low-density lipoprotein may moderate the association of baseline hs-CRP with incident cardiac events in the Asian populations

Abstract: Modified low-density lipoprotein may moderate the association of baseline hs-CRP with incident cardiac events in the Asian populations To the Editor, Baseline high-sensitivity C-reactive protein (hs-CRP) concentrations have been associated with incident cardiovascular disease in the general population, mainly in Western countries; however the association was controversial in the Asian populations [1,2]. Notably, the association was consistently present in the Asian patients with established cardiovascular dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…It has been indicated that CRP may contribute to the development of arteriosclerosis in the presence of modified low-density lipoprotein (LDL) such as oxidized LDL [19]. Lin et al explained that modified LDL may be a potential moderator for the association of hs-CRP with cardiovascular disease in Asian populations [20]. Previous reports have shown that anti-inflammatory therapy could improve clinical outcomes in CAD patients, with statins in particular shown to indirectly reduce hs-CRP along with LDL cholesterol (LDL-C), and to improve inflammation [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…It has been indicated that CRP may contribute to the development of arteriosclerosis in the presence of modified low-density lipoprotein (LDL) such as oxidized LDL [19]. Lin et al explained that modified LDL may be a potential moderator for the association of hs-CRP with cardiovascular disease in Asian populations [20]. Previous reports have shown that anti-inflammatory therapy could improve clinical outcomes in CAD patients, with statins in particular shown to indirectly reduce hs-CRP along with LDL cholesterol (LDL-C), and to improve inflammation [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…The cumulative exposure to both traditional and non-traditional CVD risk factors in older HD patients may further contribute to the development of PAS [23]. Inflammation has been involved in the development of arterial stiffness and CVD events in CKD patients [42,47]. It has been well known that serum CRP may be a mediator of the development of CVD events and post-statin therapeutic CRP levels rather than LDL were associated with subsequent CVD events [48].…”
Section: Discussionmentioning
confidence: 99%